Thermometric Studies of Newly Developed Nanolubricants - Siginer, D (American Society of Mechanical Engineers, 2016)
One of the primary requirements of space lubricants is that they have extremely low vapor pressures to withstand the space vacuum environment. Nanolubricants are known to have extremely low vapor pressure and some have attractive lubricant properties such as low coefficient of friction and good lifetimes. However, many other physical properties need to be evaluated in bringing forth new space liquid lubricants such as wide liquid temperature range and adequate heat transmission capabilities. The heat capacity and heat flow measurements for two newly developed nanolubricants Kolkhida 1 and Kolkhida 2 were conducted using Modulated Differential Scanning Calorimetry (MDSC). The experimental results revealed that the tested ionic liquids have large heat storage capacity as compare to the conventional heat transfer fluids. Copyright © 2016 by ASME.